Improving food safety in Uganda: Piloting the nudge theory to change risky practices amongst Uganda's pork handlers - International Livestock Research Institute (2022)
ILRI’s Boosting Uganda’s Investment in Livestock Development (BUILD) project, in collaboration with Vétérinaires Sans Frontièrs Germany, 17 Triggers with co-funding from the One Health Centre in Africa have developed nudges that have enabled food handlers at pork joints in Kampala, Uganda, to internalize good practices which have led to safer food despite the challenging work environment. The nudges were used to gently push pork handlers towards adopting the World Health Organization five keys to safer food.